Developing an international marketing plan for a software product company. Case: Syslore - Heikkinen, Timo (My University, 2004)
The purpose of this master’s thesis was to create an international strategic marketing plan for a start-up software product company. To divide research problem and clarify the structure of this thesis it is divided into three goals and parts respectively. First goal was to analyze software product industry and marketing of innovative software products in their early stage commercialization. Secondly, the aim was to describe essential factors and elements of strategic marketing planning and analyze different marketing plan models and approaches. Finally a strategic marketing plan for the case company was written based on findings in theory part. Source material and research methods The goals of the theoretical part were achieved by examining literacy, research and publications concerning strategic marketing, marketing planning and software product industry. In addition, academic and commercial research and literacy about high technology marketing, especially software products in their early stage of commercialization, was researched. The goals of the empirical part were accomplished by using marketing plan framework based on findings and conclusions from the theory part of this thesis. The Author worked as a marketing manager in the case-study company which gave an additional in-depth analysis to the empirical part. The research methodology was normative. The focus and exclusions This thesis focused on software product companies in their start-up stage with focus on enterprise solutions. In marketing planning focus is only on issues related to marketing and selling. Other parts that are commonly included under the theme business plan, like financing, budgeting, administration and legal issues were mostly dropped off or just superficially mentioned.
Keywords: Marketing plan; Strategic marketing planning; High Technology Marketing; Software Product Marketing; Software Industry Analysis; fi=Markkinointi|en=Marketing|